El Excentrico, 1970-02-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
February 5, 1970 [5 de febrero de 1970]. No volume or issue number. Cover has a group photograph in an office for the 23rd Annual United Food Drive Dance.